Analysis of Correlation of Factors Influencing the Strategy of Systemically Managed Organizations – Contextual Approach - Roma MARCZEWSKA-KUŹMA (Communications of International Proceedings, 2024)
The aim of the article is to present the results of a correlation analysis of factors influencing the strategy of systemically managed organizations. Due to a recognized gap concerning the lack of context analyses in enterprises with an implemented and maintained management system, the article primarily addresses this issue. The author employed the case study research method. The SWOT/TOWS method was used in the analysis of research results. Based on the analysis, a competitive strategy was determined, allowing for the use of identified opportunities conducive to the development of the examined company while minimizing the impact of weaknesses on the level of functioning of the organization. Based on the research results, it can be concluded that the implementation of the strategy should result in an increase in the pro-development potential of the company, focused on fulfilling the assumptions of the established standard in the scope of safety and the quality of health and life of employees and other interested parties. It is important to note that maintaining the management system in an unchanged and uncontrolled form can result in its obsolescence and diminished effectiveness, ultimately hindering the achievement of the enterprise's strategic objectives. The article highlights the importance of the need for dynamically adapting strategies to the changing context of a systemically managed organization's operations.
Keywords: strategic management; context of organization’s functioning; management system; SWOT/TOWS analysis.